Game Theory and Its Applications in The Global Oil Industry - Šťastný, Kryštof (2016)
This thesis will enable the reader to see how applications of game theory can help understand the development in oil market. Firstly, the thesis will introduce to the reader the foundations of game theory, a branch of microeconomics studying strategic interaction. Special focus will be put on the theory of oligopoly, the most important collusive and non-collusive models of oligopoly and their similarities and differences. Secondly, the thesis will show the reader how these theoretic models can be applied to the past development within the global oil industry, most prominently on the Organization of the Petroleum Exporting Countries. Finally, the thesis will present possible applications of game theory and some of the models to the oil market after the price decrease which started in 2014. This would help the reader assess the potential outcomes of the current crisis and possible development in the future.